2000
DOI: 10.1007/s003300051000
|View full text |Cite
|
Sign up to set email alerts
|

Value of (18F)-FDG positron emission tomography, computed tomography, and magnetic resonance imaging in diagnosing primary and recurrent ovarian carcinoma

Abstract: The aim of this study was to compare prospectively the accuracy of whole-body positron emission tomography (PET), CT and MRI in diagnosing primary and recurrent ovarian cancer. Nineteen patients (age range 23-76 years) were recruited with suspicious ovarian lesions at presentation (n = 8) or follow-up for recurrence (n = 11). All patients were scheduled for laparotomy and histological confirmation. Whole-body PET with FDG, contrast-enhanced spiral CT of the abdomen, including the pelvis, and MRI of the entire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
74
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(81 citation statements)
references
References 19 publications
2
74
1
4
Order By: Relevance
“…The sensitivity of CT in identifying patients that OCR can be achieved is around 60-70%, with varying reported specificity between 70% and 100% [17,18]. The main drawbacks of CT imaging is the inability to reliably assess the extent of disease in the supra colic compartment, porta hepatis, miliary disease over bowel mesentery and peritoneum, especially in absence of ascites [8][9][10][11]19].…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of CT in identifying patients that OCR can be achieved is around 60-70%, with varying reported specificity between 70% and 100% [17,18]. The main drawbacks of CT imaging is the inability to reliably assess the extent of disease in the supra colic compartment, porta hepatis, miliary disease over bowel mesentery and peritoneum, especially in absence of ascites [8][9][10][11]19].…”
Section: Discussionmentioning
confidence: 99%
“…CT or MRI remain the imaging modes of choice. Both have good sensitivity and specificity for the detection of recurrence (Gritzmann 1986;Kubik 2000;Low 1999). There is no role for additional CT of the chest (Sella 2001), over and above CT of the abdomen and pelvis, unless there are respiratory symptoms (Dachman 2001).…”
Section: Ca125mentioning
confidence: 99%
“…The role of radiology and imaging specialists positron emission tomography (RIS/ PET) and PET CT has yet to be fully established. In one paper PET seemed to have no benefit when compared to MRI or CT (Kubik 2000). However initial data in small series (Barzen 1990;García 2003;Grabiec 2006;Hauth 2005;Kim 2007;Mangili 2007;Nakamoto 2001;Thrall 2007;Torizuka 2002;Zhu 2002;Zimny 2001) would seem to suggest that its role is likely to be in the diagnosis of recurrence where initial CT or MRI has been inconclusive.…”
Section: Ca125mentioning
confidence: 99%
“…Some investigations have shown that the use of PET does not improve the diagnostic accuracy, while others have shown that PET can supplement the information obtained by CT and MRI (19)(20)(21)(22)(23). Some recent studies have demonstrated that for peritoneal carcinomatosis, the use of combined PET and CT may play an important role in the clinical management of patients (24,25).…”
mentioning
confidence: 99%